Digitalisasi pencatatan dan pelaporan keuangan bagi pelaku UMKM di Surabaya melalui kegiatan compassion - Gunawan, Adelynn Regina; Setyono, Yemima Caroline; Salviana, Fintacia Zelda; Malelak, Mariana Ing (Penamas: Journal of Community Service, 2024)
Micro, small, and medium enterprises (MSMEs) are one of the sectors that have experienced extensive adjustments due to the effects of the pandemic. For MSMEs to adapt to changes, creative and innovative solutions are needed. This event aims to encourage Generation Z to utilize creativity in helping MSMEs who are having difficulties with financial recordings. This event has a series of technical meeting activities so that participants can understand the event timeline and applicable regulations. Participants attended the workshop, followed by a progress report. The event ended with MSME coaching and an online bazaar. The results of this event are that MSMEs experienced efficiency and smooth business in recording and reporting their finances using Excel. On top of that, the participants can apply knowledge from learning activities by working on the projects given and then explaining their application to MSMEs. The sustainability of the activity can pay attention to obstacles, suggestions, and criticism so that activities are more innovative and impact the community.